2006
DOI: 10.1097/01.blo.0000203480.04174.0e
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Standardized Screw Fixation Technique of Ankle Arthrodesis

Abstract: Several methods of obtaining ankle fusion have been described, with numerous studies reporting on patient populations with varied diagnoses and various methods of fixation. This has led to outcome analyses that are difficult to interpret. Our hypothesis is that using a standard method of fusion, without the aid of allograft, a solid ankle fusion can be achieved in patients with end-stage ankle arthritis, and that this outcome can be reflected in standardized outcome tools. Forty-one consecutive ankle fusions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 26 publications
4
65
0
3
Order By: Relevance
“…We agree with other authors that judicious resection of remaining cartilage, sclerotic and nonviable bone while preserving the bone contours results in a highly stable fusion and avoids rotational malalignment [27,34,47,55].…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…We agree with other authors that judicious resection of remaining cartilage, sclerotic and nonviable bone while preserving the bone contours results in a highly stable fusion and avoids rotational malalignment [27,34,47,55].…”
Section: Discussionsupporting
confidence: 67%
“…The functional results as measured with the AOFAS score improved substantially as compared to the preoperative values and compare well to the recent literature (Table 2). Similarly, other authors have reported that between 88% and 98% of patients would undergo ankle arthrodesis again [11,27]. This probably reflects the patients' subjective relief of long-standing pain and disability despite residual functional restrictions.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations